2019
DOI: 10.5123/s1679-49742019000200008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Programa de Enfrentamento às Doenças Negligenciadas para o controle da esquistossomose mansônica em três municípios hiperendêmicos, Pernambuco, Brasil, 2014*

Abstract: Objective: to evaluate the implementation of schistosomiasis mansoni control actions under the Program to Combat Neglected Diseases in three municipalities in Pernambuco state, Brazil. Methods: implementation analysis was done in 2014, considering the following components-management, epidemiological surveillance, patient care, laboratorial support and health education-; direct observation and interviews were carried out with managers and technical personnel at the state, regional, and municipal levels. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
2
0
5
Order By: Relevance
“…Contingency policies lead to a review of priorities as contained in a second plan for the period 2015-2018, indicating lower adherence on the part of implementing stakeholders. 2,9,16 A literature review study of factors related to policy implementation in low and middle-income countries corroborates these findings by showing that workers tend to resist to change because it disorganizes established power structures. 17 The increase in the survey target population and in tests performed, although the latter are below the level recommended by the Ministry of Health, and the reclassification of new areas as being endemic (Health Regions IV and VIII) are related to sample-based coproscopic surveys and malacological surveys proposed by SANAR.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Contingency policies lead to a review of priorities as contained in a second plan for the period 2015-2018, indicating lower adherence on the part of implementing stakeholders. 2,9,16 A literature review study of factors related to policy implementation in low and middle-income countries corroborates these findings by showing that workers tend to resist to change because it disorganizes established power structures. 17 The increase in the survey target population and in tests performed, although the latter are below the level recommended by the Ministry of Health, and the reclassification of new areas as being endemic (Health Regions IV and VIII) are related to sample-based coproscopic surveys and malacological surveys proposed by SANAR.…”
Section: Discussionmentioning
confidence: 83%
“…29 Socio-economically precarious communities where low schooling levels together with environmental problems prevail, are characterized by these additional factors which result in these problems continuing, within a context in which reinfection is facilitated. [1][2][3][4][5][6][7]9,10,12,14,16,18,[23][24][25][26][27][28][29] The reduction in the percentage of positivity for other helminthiases may be associated with treatment with low toxicity medication (albendazole, mebendazole), which has taken place for decades in Brazil and has been reinforced by SANAR. 7,25 Data from the national survey on the prevalence of Manson's schistosomiasis and geo-helminthiases showed that periodic use of these low cost and easy to administer forms of medication is responsible for the reduction in approximately 80% of cases of other helminthiases.…”
Section: Discussionmentioning
confidence: 99%
“…A amostra final foi composta de 12 artigos apresentados no quadro a seguir (Quadro 1). Enquanto isso, em Dubeux et al (2019), revelou-se as fragilidades das ações de controle da esquistossomose do Programa de Controle da Esquistossomose, como a deficiência de educação em saúde, vista em erros de grafia, inadequações de nomenclatura, além de incorreções na descrição do ciclo da doença pela maioria dos materiais educativos. Além disso, houve menção às condições físicas inadequadas, contudo técnicos e gestores mostraram-se motivados para atuar nas ações de controle da doença previstas no programa SANAR.…”
Section: Resultsunclassified
“…Enquanto isso, em Dubeux et al (2019), revelou-se as fragilidades das ações de controle da esquistossomose do Programa de Controle da Esquistossomose, como a deficiência de educação em saúde, vista em erros de grafia, inadequações de nomenclatura, além de incorreções na descrição do ciclo da doença pela maioria dos materiais educativos. Além disso, houve menção às condições físicas inadequadas, contudo técnicos e gestores mostraram-se motivados para atuar nas ações de controle da doença previstas no programa SANAR.…”
Section: Não Informouunclassified